Tantangan dan Strategi Rekrutmen di Indonesia - Endro Puspo Wiroko (Psympathic : Jurnal Ilmiah Psikologi, 2017)
This study aims to see the current picture of recruitment in Indonesia. The research used survey method which was then analyzed thematically. Research subjects were 46 participants who worked in the field of recruitment with varied rank and seniority. The main findings related to the recruitment process are summarized based on participant responses. First, the majority of respondents argued that recruitment is currently very challenging considering on one hand the presence of less qualified candidates or even on the other hand the company does have a high enough demands. Second, given the budgetary problems, companies must adjust their recruitment strategies to their internal conditions. Finally, a recruit must have certain abilities such as target orientation, networking, negotiation, and analytic thinking. The results of this descriptive study can be used as a basis for further research and for recommendations on recruitment discussion forums. This study is limited to respondents from private companies, further research is suggested to increase the number of representative samples and develop more specific instruments.